Green plastics: Utilizing chicken feather keratin in thermoplastic polyurethane composites to enhance thermo-mechanical properties - Pourjavaheri, Firoozeh; Jones, Oliver A. H.; Mohaddes, Farzad; Sherkat, Frank; Gupta, Arun; Shanks, Robert A. (Society of Plastics Engineers, 2016)
A 'green', sustainable resource, in the form of chicken feather derived keratin, was used to enhance the thermomechanical properties of polyurethane bio-composites. Solvent–casting–evaporation method was used to incorporate three levels of chicken feather fibers (0, 10 and 20 %·w/w) into a polyurethane matrix. The thermomechanical properties of the resulting composites were then assessed using differential scanning calorimetry, thermogravimetry, dynamic mechanical analysis and stress–strain measurements with hysteresis loops. The uniformity of the dispersion of the keratin fiber in the plastic matrix was investigated via macro photography and optical microscopy. Scanning electron microscopy of fracture surfaces was used to verify that the adhesion between fiber and polymer was effective. Addition of chicken feather fibers to the polyurethane matrix was found to decrease the glass transition temperature, recovery strain and mass loss of the composites but increase the elastic modulus, storage modulus, and char level. The results demonstrate that keratin derived from what is currently a waste product from the poultry industry (with significant disposal costs) can improve the thermo-mechanical properties of composites, simply and cheaply, with potentially large environmental benefits.